2011
DOI: 10.1080/13510347.2011.563114
|View full text |Cite
|
Sign up to set email alerts
|

Unfinished business: the Catholic Church, communism, and democratization

Abstract: Although history has shown us that the church plays a role in the political liberalization of non-democratic countries, the nature of the church's role and how it participates in politics has yet to be fully revealed. By revisiting the Polish Church's historic role in the collapse of communism, I argue that we have overestimated the church's effect on political liberalization in that case, which has led us to neglect or be prematurely disappointed in its role in the remaining communist countries such as in Cub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…A public opinion survey conducted by the National Taiwan University in 1992 indicated that 56.9 per cent of respondents believed that ‘a great majority of the members of the Legislators speak for big business rather than for the common people’, and 57.2 per cent felt that ‘most candidates pledge to serve the people, but they actually only look after their self-interest’. Public outrage at corruption triggered some reform-minded politicians to push for electoral reforms in the mid-1990s, and some Kuomintang members were also in favour of change (Chu 1999). The Kuomintang suggested the idea of adopting a Japanese-style first-past-the-post mixed system in 1994, but swiftly withdrew the proposal due to opposition from other parties.…”
Section: The Electoral Reform Process In Taiwanmentioning
confidence: 99%
See 2 more Smart Citations
“…A public opinion survey conducted by the National Taiwan University in 1992 indicated that 56.9 per cent of respondents believed that ‘a great majority of the members of the Legislators speak for big business rather than for the common people’, and 57.2 per cent felt that ‘most candidates pledge to serve the people, but they actually only look after their self-interest’. Public outrage at corruption triggered some reform-minded politicians to push for electoral reforms in the mid-1990s, and some Kuomintang members were also in favour of change (Chu 1999). The Kuomintang suggested the idea of adopting a Japanese-style first-past-the-post mixed system in 1994, but swiftly withdrew the proposal due to opposition from other parties.…”
Section: The Electoral Reform Process In Taiwanmentioning
confidence: 99%
“…It was the Kuomintang that adopted the SNTV-MMD system for the 1992 Legislative Yuan election because the SNTV-MMD achieved satisfactory results for the party in local elections. SNTV-MMD had long been a link between the Kuomintang and local factions, and the single non-transferable vote and the relationship with local factions allowed the Kuomintang to enjoy a favourable proportion of the vote and to win the seats (Chu 1999). However, after the democratic transition, as the Democratic Progressive Party began to develop its electoral skills and new political parties were formed, the Democratic Progressive Party and the new parties started to increase their seats in the Legislative Yuan.…”
Section: The Electoral Reform Process In Taiwanmentioning
confidence: 99%
See 1 more Smart Citation
“…The Cuban and Polish nations are predominantly Catholic. In both cases, Catholicism is a significant component of the rural community identities, and to some extent, also national identities (Crahan, 2017;Chu, 2011;Eberts, 1998). Therefore, Cuba and Poland shared cultural patterns and culture-based identity.…”
Section: Introductionmentioning
confidence: 99%